[PP.06.27] THE EFFECT OF NIGHTTIME AIRCRAFT NOISE EXPOSURE ON CIRCADIAN BLOOD PRESSURE PROFILE. (September 2017) - Rojek, M.; Rajzer, M.; Pizon, T.; Skalski, P.; Czarnecka, D.
Abstract : Objective: Nocturnal aircraft noise as environmental stressor causes activation of autonomic and endocrine systems.That might result in changes in sleep structure and increases in blood pressure and heart rate. Aim of the study was to investigate effects of nighttime exposure to aviation noise on quality of sleep, and hemodynamic parameters-heart rate and blood pressure profile. Design and method: Study group was randomly recruited among inhabitants of area exposed to high nighttime aircraft noise levels, exceeding 50db(A). Control group was recruited accordingly in the area of low nighttime aircraft noise exposure, below 45db(A). Inclusion criteria involved age (40–65yrs) and time of residence in given area (min.3 yrs). Sites were selected based upon acoustic maps. Anthropometric and demographic data, information on habits and sleep quality were collected via questionnaire. In both groups 24 h ambulatory blood pressure monitoring (ABPM) was performed in order to determine 24 h, day and night BPs and heart rate. Based on ABPM results, participants were assigned to the dipper, non-dipper, reverse dipper and extreme dipper group. The relation between noise exposure, sleep pattern, BPs and HR was determined. Results: Study group (n = 101pts) and control group (n = 100pts) were of equal age (53.5 vs 53.6 yrs), BMI (27.2 vs 27.7 kg/m 2 ) and gender ratio (65% vs 71%women). Neither 24 h BPs nor daytime BPs did not statistically differ between groups.Nighttime BPs analysis detected difference between groups in DBPN(66.6 vs 63.6 mmHg, ) and MAPN(81.6 vs 79.1 mmHg) but no in SBPN and PPN. Heart rate was higher in study group (73.1 vs 70.3 bpm). In BP profile analysis we found physiological night BPdrop disturbance in study group- only 34%dippers vs 54% in control. Sleep quality survey revealed sleep deterioration in study group-89% suffered from poor sleep quality (difficult falling asleep, waking up at night, early waking) and consequently- presented impaired daytime performance;in comparison-42% of control reported similar disorders. Conclusions: Long-term exposure to nighttime aircraft noise is associated with sleep disturbance and physiological circadian blood pressure profile alterations. The effect might be partially masked by habituation to noise.However, biologic adaptation is often incomplete and requires physiologic resources therefore putting strain on organism as whole.